The Effect of Using the Flipped Learning Strategy on Developing Reading Comprehension Skill in English among 4th Grade Primary Students in Kuwait - Bedour Alshati; Ahmad Hamad Al-Khawaldeh (European Scientific Journal, ESJ, 2023)
This study investigated the effect of using flipped learning strategy in developing reading comprehension skill in English language among 4th grade primary students in the Kuwaiti capital schools. To achieve the study’s objective, the researcher used the quasi-experimental approach, which depends on the selection of an experimental and a control group. To calculate the effect, a post-achievement test was applied to the members of the two groups, and the study sample was intentionally selected, and so consisted of (50) male and female students from the basic stage. The data were analyzed statistically, and the results revealed that there were statistically significant differences in the average achievement of the experimental group on the post application. To test these differences, the analysis of covariance was applied. Based on the obtained results, the researcher recommended applying flipped learning strategy in teaching English and related subjects in primary schools in the State of Kuwait and also holding training courses for English language teachers to design lessons that align with the flipped learning strategy.